Konsep Etos Kerja Muslim, 5R dan Relevansinya terhadap Karakter 3T Mahasiswa Akademi Komunitas Toyota Indonesia - Imanuddin Kamil; Akmal Amir; Dedi Ambari (Departement of Mathematics Education, 2022)
This article aims to find out the concept of the Muslim work ethic, 5R and its relevance to the 3T character of Indonesian Toyota Community Academy students. The research method used is library research using a content analysis approach, namely in the form of descriptive-analytical reading of various primary and secondary sources. Global competition in the industrial world is getting faster and tighter. The company's need for reliable human resources capable of winning the competition is very large. PT. Toyota Motor Manufacturing Indonesia (TMMIN) as one of the well-known automotive industry companies is very serious in preparing human resources by establishing the Toyota Indonesia Community Academy under the umbrella of the Toyota Indonesia Foundation. Its vision is to produce graduates who are Tanggap (Perceptive), Tangkas (Agile) and Tangguh (Perseverance). As a Japanese company, PT. Toyota implements a 5R work culture (Ringkas, Rapi, Resik, Rawat, Rajin) adopted from the Japanese 5S work culture (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). This work attitude is also applied in coaching students to develop Soft Skills and Hard Skills. Islam is a universal and comprehensive religion that contains and summarizes all aspects of life. The spirit and motivation of Islam has influenced various sectors of life. In the world of work, Islamic principles and values give birth to a distinctive work ethic; as a Muslim's self-actualization of the teachings and principles he believes in (QS. 62:10), a representation of enthusiasm and work motivation based on the spirit of worshiping Allah SWT (QS. 51:56), as a manifestation of good deeds (QS. 41: 46). This research resulted in the finding that there is an intersection of the concept of a Muslim work ethic based on good deeds (QS. 2:177) with a 5R work attitude which is a derivative of Japanese culture kaizen (continuous improvement). Likewise, it was also found that the relevance of the Muslim work ethic and 5S work attitude to the 3T character of AKTI students.